Capsazepine prolongation of the duration of lidocaine block of sensory transmission in mice may be mediated by modulation of HCN channel currents - Zhao, Wenling; Liang, Peng; Liu, Jin; Li, Huan; Liao, Daqing; Chen, Xiangdong; Li, Qian; Zhou, Cheng (PeerJ (San Francisco, CA), 2019)
Hyperpolarization-activation cyclic nucleotide-gated (HCN) channels contribute to the effects of lidocaine. Capsazepine (CPZ), a competitive inhibitor of capsaicin of transient receptor potential vanilloid-1 channel, has also been found to inhibit HCN channel currents ( ). This study was designed to investigate whether CPZ could prolong durations of lidocaine in regional anesthesia. Mouse HCN1 and HCN2 channels were expressed in human embryonic kidney 293 (HEK 293) cells. The effect of CPZ on was measured by whole-cell patch-clamping recording. Sciatic nerve block model in mice was used for the study in vivo. The mice were randomly divided into seven groups, respectively, receiving lidocaine, CPZ, ZD7288 (HCN channel blocker), CPZ + lidocaine, ZD7288 + lidocaine, ZD7288 + CPZ + lidocaine, forskolin (an activator of adenylyl cyclase) + CPZ + lidocaine. Regional anesthetic durations of lidocaine were determined. Voltage-gated sodium channel currents ( ) and were recorded in dorsal root ganglion neurons of mice. The effects of CPZ on and with or without Cyclic adenosine monophosphate (cAMP) were assessed. Isolated mice sciatic nerve was prepared to evaluate the effect of CPZ on the compound action potentials (CAP). Capsazepine non-selectively inhibited transfected mHCN1 and mHCN2 channel currents in HEK 293 cells. In sciatic nerve block in vivo, compared to lidocaine alone, adding CPZ extended the durations of lidocaine for noxious sensory block (35.1 ± 3.3 vs. 20.3 ± 1.7 min), tactile sensory block (25.5 ± 4.4 vs. 20.0 ± 3.7 min), thermal sensory block (39.6 ± 6.6 vs. 26.8 ± 5.5 min), and motor function block (28.6 ± 4.1 vs. 20.9 ± 4.2 min). Duration of thermal sensory block was longer in CPZ + lidocaine group than that of ZD7288 + lidocaine group (39.6 ± 6.6 vs. 33.4 ± 4.5 min). Forskolin reversed the prolongation by CPZ on lidocaine durations. CPZ or ZD7288 alone did not produce typical regional anesthetic effects. Increased intracellular concentration of cAMP reversed the inhibition of CPZ on . Although CPZ alone inhibited at the concentration more than 30 μM, it did not inhibit the CAP amplitudes in isolated sciatic nerves. CPZ dose-dependently enhanced the inhibitory effect of 1% lidocaine on the CAP amplitudes. Capsazepine may prolong durations of lidocaine in peripheral nerve block by modulation of HCN channel currents.